Imaging techniques in acute pancreatitis - Wolf, R; Ploeg, R; Gooszen, H; Van der Jagt, E (2001)
Acute pancreatitis is a potentially severe disease with a high morbidity and mortality rate. The natural history of acute pancreatitis is characterised by a variable clinical picture ranging from a mild and self-limiting disease to a necrotising form with various severe and potentially lethal complications. The use of early and reliable diagnostics in the detection of (infected) pancreatic necrotic tissue in the treatment of acute pancreatitis allows adequate supportive treatment to be initiated before the onset of complications, such as infection of the pancreatic necrotic tissue or multiple organ failure. Contrast-enhanced CT is currently the gold standard in the detection of necrosis. Because of some diagnostic shortcomings and disadvantages associated with this technique, such as the use of ionising radiation and the potential nephrotoxicity of the contrast agents, reliable alternative (imaging) techniques are being sought. In particular, contrast-enhanced MRI may play an increasingly important role in the future diagnostics of acute pancreatitis.